Improve Awareness of the Forensic Odontology among Medical Graduates: Need of the Hour? (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Forensic odontology is a fastly growing field in both dental and forensic sciences. It involvesthe application of principles and expertise of dental sciences for criminal investigations. With increasingdemand and use of dental evidence in forensic examinations, proper knowledge and awareness of the subjectis more necessary than ever before.Materials and Method: A survey was conducted in Medical and Dental colleges in and around Mangalore,Dakshina Kannada after approval from institutional ethics committee. It included MBBS and BDS students(III year to internship)Result: The analysis of the data showed two fold results. Knowledge of tooth as a source of DNA, evidencefor natural disasters in personalle identification was equal among the graduates. Medical graduates hadhigher awarenes of certain aspects like barr bodies and anthropometry whereas; Dental graduates wereaware of the odontology aspects in identification of cases of rapes, child abuse, techniques like forensicradiology, bite mark analysis and sexual dimorphism in teeth.Conclusion: The study highlighted the difference in knowledge of forensic odontology between medical anddental students. It emphasized on the need of increasing awareness of the subject among medical graduatesand to help them understand the role of their peers from the dental fraternity in forensic sciences. The studyalso stressed on the need of a forensic odontologist in the State Forensic Team.